(untitled) (Bangladesh Journal of Medical Science, 2015)
Background: Total anomalous pulmonary venous return (TAPVR) is an uncommon congenital cardiovascular anomaly with poor natural prognosis without proper intervention. It has been detected more frequently in recent year due to the advent of echocardiography. The aim of this study is to evaluate the clinical manifestations, age at diagnosis and short term outcomes in TAPVR patients. Methods: From 1st January 2013 to 31st December 2013, a total of 34 cases with TAPVR were admitted in pediatric cardiac centre at Dhaka Shishu Hospital, Dhaka, Bangladesh. All of them were evaluated with 2-dimensional (2-D) and color Doppler echocardiography examination. CXR and ECG were also done. Patients sex, age at diagnosis, types of TAPVR, clinical manifestations, radiological finding, ECG findings and outcomes were compiled and analyzed. Results: In 34 patients with TAPVR, 23 (67.6%) were male and 11 (32.4%) were female with male to female ratio of 2.09:1. Most of the patients were diagnosed between 0-6 months of age that is 13 (38.2%) cases were in 0-2 months age group, 14 (41.2%) cases were in more than 2 months to 6 months age group. Tachypnea and cyanosis were more common symptoms. The types of TAPVR was supra-cardiac 18 (52.9%), cardiac 11 (32.4%), infra-cardiac 3 (8.8%) and mixed in 2 (5.9%) cases. Pulmonary hypertension was present in 31 (91.2%) of 34 cases. Among them, 20 (58.8%) patients had severe pulmonary hypertension. The most common associated intra-cardiac lesions of TAPVR patients were ASD 13 (38.2%) and PFO 13 (38.2%). ECG findings of TAPVR, 18 (52.9%) patient had right axis deviation (RAD), right ventricular hypertrophy (RVH) and 14 (41.2%) had right axis deviation (RAD), right ventricular hypertrophy (RVH), right atrial enlargement (RAE). X-ray findings of TAPVR patients, 32 (94.1%) patients had Cardiomegaly and increased pulmonary vascularity. Among admitted patient, 3 (8.8%) patients died due to pneumonia and intractable heart failure, 31 (91.2%) patients referred to advanced cardiac centre for operative treatment. Conclusions: Tachypnea and Cyanosis were an obvious clinical symptom of TAPVR. 2-D and color Doppler echocardiography can provide quick and accurate diagnostic information of TAPVR. Death rate is high in TAPVR patient in spite of adequate medical management. So, early detection and definitive surgical treatment of TAPVR is much needed. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.270-273